Happiness and poverty in developing countries : a global perspective - Dowling, J. Malcolm (John Malcolm); Yap, Chin-Fang (Palgrave Macmillan, 2013)
By carefully analyzing a comprehensive data base of questionnaire responses gathered over the past two decades in the developing regions of Africa, Asia and Latin America, this book arrives at a series of powerful conclusions regarding the determinants of well-being and happiness of all sectors of society. The book explores the relative importance of health and education, as well as addressing social and demographic issues surrounding happiness, and the effect of ageing. Psychological factors are also discussed, such as the effects of a belief in social mobility in the less well-off. The authors explore why income poverty is not the only form of poverty, and focus on other factors that uplift the well-being and happiness of the underprivileged.